A case study of good practices at diversity and inclusion management - Ripado, Luis Miguel; Jorge, Fátima; Dionísio, Andreia (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The scope of this research concerns the theme of diversity and inclusion and values and behaviors, and it purpose is to define and validate a theoretical model which allows the relationship of Diversity and Inclusion (D&I) with Values and Behaviors (V&B) and its repercussion in Organizational Performance. This case study is supported by variables from different european affiliates of Novartis Pharmaceuticals.